Isolation and immunological characterization of rhoptries from Neospora caninum - Martins, Thais Agostinho; Barros, Luiz Daniel De; Nino, Beatriz De Souza Lima; Bernardes, Juliana Correa; Silva, Ana Clécia Dos Santos; Minutti, Ana Flávia; Cardim, Sergio Tosi; Rose, Milena Patzer; Martinez, Valentina; Garcia, João Luis (Brazilian Journal of Veterinary Research and Animal Science, 2024)
Neospora caninum is a parasite that causes considerable loss in cattle production. Understanding its infection mechanisms is essential to comprehend its impact on herds. Cell fractionation and characterization of the fractions could contribute to the selection of proteins and organelles with immunogenic characteristics. Thus, the present study aimed to isolate rhoptry and subcellular fractions of N. caninum using a sucrose gradient and characterize their immunogenicity in mice. Tachyzoites of the Nc-1 strain were cultured in VERO cells, fractionated by glass beads, and ultracentrifuged in a sucrose gradient ranging from 0.25–1.8 M. The fractions were characterized using transmission electron microscopy. Each fraction was inoculated with Quil-A adjuvant (20 μg) into mice to produce polyclonal antibodies for immunofluorescence cell culture and Western blotting. Ultracentrifugation resulted in three distinct fractions (F1, F2, and F3) and a pellet. Fraction one (F1) at 1.0 M concentration contained parasite membranes, F2 at 1.4 M contained rhoptry and conoid, F3 at 1.6 M contained mitochondria, and the pellet at 1.8 M fraction contained cell debris. The four fractions exhibited the same bands with molecular weights of 50, 51, 52, and 62 kDa. Only F2 showed rhoptry structures and a 54 kDa protein resembling NcROP2. This study successfully separated subcellular fractions of N. caninum through processing and ultracentrifugation, identified rhoptry structures, and determined specific protein weights of each fraction.